Linkages in the landscape : - Bennett, Andrew F. (IUCN--the World Conservation Union, 2003)
The loss and fragmentation of natural habitats is one of the major issues in wildlife management and conservation. Habitat corridors are sometimes proposed as an important element within a conservation strategy. Examples are given of corridors both as pathways and as habitats in their own right. Includes detailed reviews of principles relevant to the design and management of corridors, their place in regional approaches to conservation planning, and recommendations for research and management